2009
DOI: 10.1111/j.1365-2389.2008.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon additions: effects on soil bio‐physical and physico‐chemical properties

Abstract: The effects of organic carbon (OC) additions from farm manures and crop residues on selected soil biophysical and physico-chemical properties were measured at seven experimental sites, on contrasting soil types, with a history of repeated applications of farm manure or differential rates of inorganic fertilizer nitrogen (N). Repeated (> 7 years annual additions) and relatively large OC inputs (up to 65 t OC ha À1 ) were needed to produce measurable changes in soil properties, particularly physical properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
73
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 40 publications
13
73
0
Order By: Relevance
“…Total soil porosity was calculated assuming particle density 2.65 g cm -3 using the following equation (Bhogal et al, 2009): Total soil porosity = [1-(bulk density/2.65)] 100%. (1) The aggregate size distribution of each treatment was determined using the same core samples that were used to calculate the bulk density.…”
Section: Methodsmentioning
confidence: 99%
“…Total soil porosity was calculated assuming particle density 2.65 g cm -3 using the following equation (Bhogal et al, 2009): Total soil porosity = [1-(bulk density/2.65)] 100%. (1) The aggregate size distribution of each treatment was determined using the same core samples that were used to calculate the bulk density.…”
Section: Methodsmentioning
confidence: 99%
“…For example, changes in the total SOC pool have been shown to depend on the amount of organic material (C) applied, but not on the type of material (e.g., Rasmussen et al, 1980) whereas there is conflicting evidence on the response of other soil properties to the type of material applied. For example, Bhogal et al (2009) observed that repeated OC inputs (for at least 7 years) in the form of livestock manures led to improvements in soil physical properties (bulk density, porosity, and available water capacity) whereas OC additions in the form of crop residues (straw) did not. By contrast, Peltre et al (2015) measured changes in specific draft force that were related to the amount of OC applied and its effect on bulk density rather than due to differences in the type of organic material (including compost, livestock manures and sewage sludge applied annually over 11 years).…”
Section: Introductionmentioning
confidence: 99%
“…The application of organic materials to agricultural soils is a widely recommended practice not only as a source of essential plant nutrients which can provide savings in inorganic fertilizer use (Defra, 2010), but also as a means of increasing soil organic carbon (SOC) levels with associated improvements in soil biological and physical functioning (Bhogal et al, 2009). Indeed, the benefit of a range of organic material applications (livestock manures, composts, biosolids, etc.,) for SOC and soil quality has been widely documented and reviewed (e.g., Edmeades, 2003;Johnston et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…If the C/N ratio of residue >24, available soil N is consumed by microbes and this retards decomposition rate. A number of authors have reported linear increases in SOC related to the amount of organic matter applied, whilst others, have reported that the rate of SOC accumulation is dependent on the source of organic carbon [14][15][16]. This greatly suggests the lowest (15 mm) average rainfall received in June and the highest (108 mm) in January.…”
Section: Introductionmentioning
confidence: 96%